2014
DOI: 10.1002/hipo.22297
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in temporal lobe epilepsy: Role of online and offline processing of single cell information

Abstract: Cognitive impairment is a common comorbidity in temporal lobe epilepsy (TLE) and is often considered more detrimental to quality of life than seizures. While it has been previously shown that the encoding of memory during behavior is impaired in the pilocarpine model of TLE in rats, how this information is consolidated during the subsequent sleep period remains unknown. In this study, we first report marked deficits in spatial memory performance and severe cell loss in the CA1 layer of the hippocampus lower sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 90 publications
1
22
0
Order By: Relevance
“…This is in line with an earlier pilot study of forgetting in epilepsy [111] and further supported by animal studies, as rat models of TLE show normal replay of behavior-driven sequences of single cell hippocampal activity during sleep [112]. In contrast, these three studies suggest that activity during periods of wakefulness following learning, possibly within the first few hours [113], may be more closely linked to ALF, as would be predicted by interference-based models of amnesia (e.g., [114,115]).…”
Section: Possible Mechanisms For Alfsupporting
confidence: 89%
“…This is in line with an earlier pilot study of forgetting in epilepsy [111] and further supported by animal studies, as rat models of TLE show normal replay of behavior-driven sequences of single cell hippocampal activity during sleep [112]. In contrast, these three studies suggest that activity during periods of wakefulness following learning, possibly within the first few hours [113], may be more closely linked to ALF, as would be predicted by interference-based models of amnesia (e.g., [114,115]).…”
Section: Possible Mechanisms For Alfsupporting
confidence: 89%
“…Previous studies have shown that TLE rats have poor spatial memory performance accompanied by decreased place field stability and increased out‐of‐field firing of hippocampal place cells . This suggests that while spatial coding by place cells in the hippocampus is disrupted, temporal coding remains intact . Thus, it has been proposed that while the integration of place cells into spatial processing networks in TLE rats is intact, the original representation is unreliable .…”
Section: Discussionmentioning
confidence: 99%
“…Although lesions are found in many brain areas, this type of epilepsy is usually associated with significant hippocampal damage (Bartolomei et al, ; Blümcke et al, ; Coras & Blümcke, ). Unsurprisingly, temporal lobe epilepsy often provokes cognitive decline and memory deficits in both human patients (Dinkelacker, Xin, Baulac, Samson, & Dupont, ; Giovagnoli & Avanzini, ; Halgren et al, ; Hennion et al, ; Rayner, Jackson, & Wilson, ; Titiz, Mahoney, Testorf, Holmes, & Scott, ) and animal models (Armstrong et al, ; Faure et al, ; Häussler, Rinas, Kilias, Egert, & Haas, ; Kalemenev et al, ; Zhang, Thamattoor, LeRoy, & Buckmaster, ). Unfortunately, the mechanisms of these deficits and dysfunctions are not yet fully understood and no effective treatment for seizure prevention exists at present.…”
Section: Introductionmentioning
confidence: 99%